Visual Outcome of Phacoemulsification versus Small Incision Cataract Surgery in Pseudoexfoliation Syndrome – A Pilot Study - Naik, Anmol Ulhas (J Clin Diagn Res, 2017)
INTRODUCTION: Available data has highlighted the efficacy of both Phacoemulsification (PHACO) and Small Incision Cataract Surgery (SICS) in the presence of Pseudoexfoliation (PEX) syndrome. In developing countries, both are commonly performed procedures for cataract extraction. But, no direct comparison between these two procedures is available in the setting of PEX syndrome. With this lacuna in mind, this pilot study decided to compare the visual outcomes of both these techniques in the setting of PEX syndrome. AIM: To compare and analyze the efficacy and safety of PHACO versus SICS in patients of PEX syndrome who underwent cataract surgery. MATERIALS AND METHODS: A prospective, conveniently sampled, observational, pilot study was conducted over six months in ophthalmology department of a tertiary eye institute in India. A total of 200 eyes of 100 patients conforming to pre-defined criteria were conveniently sampled and allotted to two groups of 50 patients each. First group underwent PHACO and second underwent SICS. The demographic profile, pre-operative, intra-operative and post-operative details and complications as well as visual acuity were recorded. Data obtained was analyzed using chi-square test. Statistical significance was set at 95% Confidence Intervals (CI), i.e., at a p-value of <0.05. RESULTS: Of 76 males and 24 females, the mean age was 67.95 years. No statistically significant differences were observed between PHACO and SICS groups with regards to intra-operative complications {overall n=13 in PHACO versus n=21 in SICS, p=0.13}. Controlled sphincterotomy was required in a significantly higher number of SICS cases (p=0.03). No statistically significant differences were observed in terms of post-operative complications (overall n=5 in PHACO versus n=10 in SICS, p=0.26). CONCLUSION: With careful pre-operative assessment, due to intra-operative modifications and surgical expertise, both PHACO and SICS are apparently safe procedures in PEX syndrome.